Agribusiness and Supply Chain Development Policies in Nepal: A Review from Temporal Dynamics - Mishra, Rajendra Prasad; Paudel, Indra Hari (Nepal Public Policy Review, 2023)
A critical review of agriculture policies during different plan periods, aligned with political changes, has been conducted out to understand the shift in priorities, technology transfer ,support products, and private sector engagement. Firstly, in the 1950s, the policies were influenced by the first five-year plan and focused on the import and dissemination of technology. During the three decades of the Panchayat era, there was an emphasis on state mechanisms for technology transfer, agribusiness, and research, with limited incentives for the private sector. After 1990, agricultural policy products followed a path of liberalization and focused on defining the state’s role and promoting pluralism. This period witnessed the establishment of a wide range of private and cooperative-led agribusinesses, although their growth was hindered by political conflict. Subsequently, policies began to incorporate priorities such as nutrition security, comparative advantage, competitiveness, climate change adaptation, agrobiodiversity conservation, and sustainability. However, with the federalization of the state and establishment of a three-tier governance system in 2015, agriculture policies, priorities and strategies a became fragmented, diversified, and localized, and lack harmonization. This review demonstrates that agriculture policies were largely influenced by domestic political developments and structural changes at the international level. Nonetheless, a consistent focus on increasing production and productivity, as well as achieving food security and self-sufficiency, can be observed.. Throughout all policy periods, supply chain development, a crucial component of agribusiness, received limited prioritization, which remains a major impediment to agricultural transformation. Despite seven decades of policy evolution, Nepal has been unable to create an enabling policy environment to attract significant private and cooperative sector investments that could drive substantial growth in agribusiness. This situation calls for further research in the field of policy formulation capacity among the three tiers of government to foster agribusiness and promote supply chain development for agricultural transformation.